INFLUENCE OF DYNAMICAL ERRORS DURING COORDINATE’S MEASURING, IONOSHERE AND TROPOSHERE DELAY FOR NAVIGATION DEFINITION OF AIRSHIPS BY HELP OF SRNS - D. A. Zatuchny (Научный вестник МГТУ ГА, 2016)
The article analyses the influence of dynamical errors, ionospherie and tropospherie errors on navigational definition of aircraft. The quantity of these errors for the Tumen region is cited. Comparative analysis of these errors is given.